The Influence of Organizational Commitment and Training on Employee Performance Through Loyalty as a Moderating Variabel - Muhammad Fauzy Hamdani; Yanda Bara Kusuma (International Journal of Economics Development Research (IJEDR), 2024)
Human resources play a crucial role in the success of organizations. This research aims to determine the influence of organizational commitment and training variables on employee performance, as well as the moderating role of loyalty variable in influencing the relationship between organizational commitment, training, and employee performance. The data used are primary data obtained from questionnaires distributed to the research sample. The population in this study consists of all employees of CV. Litera Jannata Perkasa. A sample of 68 respondents was selected using purposive sampling technique. Data were analyzed using Moderated Regression Analysis technique. The research findings indicate that partially, organizational commitment and training significantly influence employee performance, while training does not have a significant effect. However, in the regression analysis test results, loyalty moderates the influence of organizational commitment on employee performance. Conversely, loyalty is unable to moderate the influence of training on employee performance. These findings provide valuable insights into the factors affecting employee performance in companies and offer implications for practice by providing guidance to enhance human resources at CV. Litera Jannata Perkasa and similar companies.